The Development of Port Cities and Regions as a Subject for Interdisciplinary Cooperation. The Contribution of Historical Analysis. (Res Gesta, 2025)
The evolution of research in maritime and port history over the last thirty years shows a growing openness to dialogue and interdisciplinary cooperation, with professionals joining international networks on the subject that favour comparative study on a broader spatial scale. This article analyses how this process has operated and the identification in historiography, since the mid-20th century, of the role of port cities in global processes, by way of an introductory approach. It also argues the potential of addressing the dynamics of these cities to understand the development of port regions and territories, presenting itself as a conducive environment for multidisciplinary, interdisciplinary, and transdisciplinary dialogue on aspects that contribute to the resolution of global problems of increasing complexity, connectivity, and feedback.
Keywords: Cities; Ports; Globalisation; Development; Historiography